Knowledge, Family Support, and the Role of Healthcare Professionals as Determinants of Pregnant Women’s Participation in Prenatal Yoga - Sari, Rury Narulita; Hardika, Mufida Dian (FORIKES, 2026)
Pregnancy-related discomfort is associated with decreased quality of life and an increased risk of complications extending to the time of delivery. One complementary midwifery service that serves as a promotive and preventive non-pharmacological intervention to reduce such discomfort is prenatal yoga, which is influenced by factors including knowledge, family support, and the role of healthcare professionals. This study aimed to analyze the determinants of pregnant women’s participation in prenatal yoga activities at an independent midwifery practice. A cross-sectional design was employed, involving 24 pregnant women who attended antenatal care. Data were collected using a structured questionnaire and analyzed using Chi-square test. The results indicated that the prevalence of participation in prenatal yoga was relatively high, at 70.8%. The p-values for each determinant were as follows: knowledge (p = 0.001), family support (p = 0.020), and the role of healthcare professionals (p = 0.007). It can therefore be concluded that knowledge, family support, and the role of healthcare professionals are positive determinants of pregnant women’s participation in prenatal yoga.Keywords: knowledge; family support; role of healthcare professionals; prenatal yoga